"CAD‐on" Interfaces – Fracture Mechanics Characterization. Issue 9 (30th October 2019) - Walker, Peter David; Ruse, N. Dorin
Abstract: Purpose: To apply fracture mechanics methodology to determine the interfacial fracture toughness of the interfaces present in "CAD‐on" crowns consisting of CAD/CAM milled lithium disilicate veneers glass‐fused to CAD/CAM milled yttrium oxide stabilized tetragonal zirconia polycrystal framework. Materials and Methods: The notchless triangular prism specimen fracture toughness test was used to determine interfacial fracture toughness. Four groups, each consisting of (6 × 6 × 6 × 12) mm prisms (n = 22), were produced. Half‐size [(6 × 6 × 6 × 6) mm] specimens of IPS e.max CAD and IPS e.max ZirCAD were approximated under vibration with Crystal Connect fusing glass and sintered according to manufacturer's guidelines to obtain the following three interfaces: (1) e.max CAD/Crystal Connect/e.max CAD (Group I); (2) Zir CAD/Crystal Connect/Zir CAD (Group II); and (3) Zir CAD/Crystal Connect/e.max CAD (Group III). For Group IV (control, based on the "press‐on" veneering technique), half‐size [(6 × 6 × 6 × 6) mm] IPS e.max ZirCAD prisms were coated with ZirLiner and pressed with IPS e.max ZirPress ingots to obtain (6 × 6 × 6 × 12) mm prisms. All specimens were tested using a computer controlled material testing machine. Results were analyzed with one‐way ANOVA, Scheffé multiple means comparisons (α = 0.05) and Weibull statistics. All fractured surfaces were characterized with a light microscope. Selected fractured surfaces were characterized under a scanning electron microscope. Results: All experimental groups demonstrated a cohesive mode of failure in the fusing glass layer. The number and size of defects appeared to correlate with the variability of fracture toughness values. There were no significant differences between the fracture toughness of the "CAD‐on" interfaces ( p = 0.052). The results suggested that the fracture toughness of Crystal Connect limited the interfacial fracture toughness values. The "CAD‐on" fracture toughness value (Group III) was significantly greater than that of the ZirPress "press‐on" control (Group IV) ( p < 0.001). Conclusion: The "CAD‐on" process results in stronger bonding between veneer and framework, compared to conventional veneering. The clinical use of "CAD‐on" crowns could therefore be advocated. The selection of any restorative material requires a thorough analysis of advantages, limitations and results from clinical studies to inform the clinical decision in a case‐by‐case approach.